The Impact of State Expenditure on Education and on Student Academic Achievement - Zh. T. Kushebayev; G. S. Nygymetov (Экономика: стратегия и практика)
Due to the impact of quarantine measures against COVID-19, the quality of education in the country’s schools has decreased. This issue is relevant and is on the agenda from the administration of the Head of State to university rectors and teachers, school principals and educators, students and their parents. Most of the participants in the discussion believe that too little money is allocated to the school. This article examines the impact of government spending on education and on students’ academic achievements. According to the literature review, it was revealed that an increase in financial support for secondary schools from the state will lead to an increase in the quality of education. To solve these research questions, we used a correlation analysis between student academic performance and government spending, and household spending. On the basis of the selected variables, a correlation analysis was carried out by the method of rank correlation of the relationship between student performance and the amount of state funding for education. The study concluded that the success of students in education is influenced by non-financial factors, such as educational standards and appropriate teaching methods. At the same time, a paradoxical situation has been revealed, almost every year the government increases annual spending on education in secondary schools, but student academic performance is constantly falling. In addition, there was no strong statistical relationship between student performance and the amount of State funding for education. Therefore, the question arises about the effectiveness of the use of allocated public funds for education.